Implementasi Patch Aromaterapi Stroberi Terhadap Penurunan Nyeri Pada Pasien Post Operasi Sectio Caesarea - Bintang Tata Praditya; Dwi Novitasari; Amin Susanto (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Postoperative pain is common after Caesarean section and may delay recovery. Strawberry aromatherapy patches offer a complementary non-pharmacological approach by promoting relaxation, improving patient comfort, and reducing pain perception. Objective: this communityservice activity aimed to evaluate the implementation of strawberry aromatherapy patches in reducing pain intensity in patients following a cesarean section. In addition, this study also examines the influence of respondent characteristics—including age, parity, and delivery history—on the reduction in pain levels experienced by patients. Method: This community service activity involved 30 post-Caesarean section patients in the Bougenville Ward. Strawberry aromatherapy patches were applied for 6–8 hours, and pain intensity was assessed using the Visual Analog Scale (VAS) before and after the intervention. Data were analyzed using descriptive statistics and the Wilcoxon signed-rank test. Results: The findings demonstrated that strawberry aromatherapy patches effectively reduced pain intensity among the 30 participating patients. Normality testing showed that pre-intervention pain scores were not normally distributed (p = 0.037), whereas post-intervention scores were normally distributed (p = 0.192), indicating different distribution patterns before and after the intervention. Conclusion: The application of strawberry aromatherapy patches reduced postoperative pain intensity in patients following Caesarean section, with mean pain scores decreasing from 5.35 before the intervention to 3.17 afterward. These findings suggest that strawberry aromatherapy patches may serve as a practical complementary non-pharmacological approach to postoperative pain management.